Optimizing Website Ranking Using Long-Tail Keywords and Internal Linking: A Case Study - Memet Sanjaya; Rizaldi Putra; Deni Utama; Arif Prayoga (SEULANGA SYSTEM PUBLISHER, 2025)
This study proposes a structured and cost-effective Search Engine Optimization (SEO) strategy through the application of long-tail keyword targeting and internal linking. Conducted across three websites within the same corporate group, this research investigates how internal links and keyword mapping can collectively improve organic rankings. Each high-volume keyword was developed into long-tail variations and implemented into topic-specific articles, supported by contextual internal and cross-site linking. Website A, as the parent site, was used strategically to distribute link authority to other sites. In a two-month observation, keyword rankings showed significant improvements, particularly for underperforming domains. The results confirm that collaborative SEO using content relevance and internal link equity distribution can enhance visibility without relying on paid backlinks.